Theoretical Assessment of the Effect of Vertical Dispersivity on Coastal Seawater Radium Distribution - Lamontagne, Sébastien; Webster, Ian T. (Frontiers in Marine Science, 2019)
Trends in radium (Ra) activity in coastal seawater are frequently used to infer submarine groundwater discharge. In general, unlike in the deep oceans, Ra samples are only collected from the surface of the mixed layer in coastal areas. The assumption is that the water column is well mixed, as often evidenced by uniform temperature and salinity profiles. However, if the timescale for vertical mixing is similar to or less than the timescale for radioactive decay, the vertical profiles in Ra activity may not be uniform. In the present work, a two-dimensional dispersion model was developed to evaluate the potential effects of slow vertical mixing on Ra distribution in the mixed layer of an inner shelf. The variables considered were the vertical coefficient of solute dispersivity (Kz), the offshore coefficient of solute dispersivity (Kx), the coastal Ra flux (Fo), the benthic Ra flux (FB), and the slope of the seabed. The shorter-lived Ra isotopes (223Ra and 224Ra; t1/2 = 3.66 and 11.4 days, respectively) were sensitive to Kz when its value was low (<10–4 m2 s–1), resulting in complex activity patterns in the water column as a function of the other variables. Ra-228 (t1/2 = 5.75 years) was only moderately impacted by low Kz but the long-lived 226Ra (t1/2 = 1600 years) was insensitive to Kz. Surface water samples may not always be representative of water column Ra activity when Kz is low, which will need to be taken into account in future field programs for seawater Ra distribution in shelf environments.